Reversal Learning Performance in the XY∗ Mouse Model of Klinefelter and Turner Syndromes - Aarde, Shawn M.; Hrncir, Haley; Arnold, Arthur P.; Jentsch, James D. (Frontiers in Behavioral Neuroscience, 2019)
Klinefelter syndrome (KS; 47, XXY) and Turner syndrome (TS; 45, XO) are caused by two relatively common sex chromosome aneuploidies. These conditions are associated with an increased odds of neuropsychiatric disorders, including attention deficit/hyperactivity disorder (ADHD), as well as impairments in cognition that include learning delays, attentional dysfunction and impulsivity. We studied cognitive functions in the XY* mouse model, which allows comparison of XXY to XY males (KS model), and XO to XX females (TS model). We evaluated adult mice with and without gonads, using a version of an operant reversal-learning task (RLT) that can be used to measure various facets of learning, impulsivity and attention. In the KS model, only one measure related to impulsivity -- perseverative responding under reversal conditions -- reliably discriminated gonadally intact XXY and XY mice. In contrast, a fundamental learning impairment (more trials to criterion in acquisition phase) in XXY mice, as compared to XY, was observed in gonadectomized subjects. No other task measures showed differences consistent with KS. In the TS mouse model, XO mice did not show a pattern of results consistent with TS, similar to past observations. Thus, the application of this RLT to these XY* models reveals only limited behavioral impairments relevant to KS.